5. EVALUASI KINERJA SBY-JK DALAM MENGATASI KEMISKINAN - Erowati, Dewi (FORUM, 2007)
Poverty is a serious problem in every country, included Indonesia. Elected Susilo Bambang Yudhoyono-Jusuf Kalla (SBY-JK) as President and Vice President by directly, poverty had place as main priority national policy. For SBY-JK leadership, poor total add more 1.78% (39.05 million in 2006, before 35.10 million). Because poverty line move up 18.39% than before, beside that this is influence economy factor. Activity to cut down on poverty as same as before government except cash assistance and poor help insurance.